Hypertension Management for Elderly People in Purbayan Village, Sukoharjo: A Community-Based Educational Intervention: Penanganan Hipertensi Pada Lansia Di Desa Purbayan, Sukoharjo: Intervensi Edukasi Berbasis Komunitas - witriyani (Bhakti Sabha Nusantara, 2025)
Hypertension is one of the most common chronic diseases affecting the elderly population in recent years. Prompt management of hypertension is essential due to its long-term consequences, which may lead to severe health conditions such as heart disease and stroke. Health education and counseling interventions are crucial in assisting elderly individuals with hypertension in managing their condition effectively. These interventions are particularly important for this demographic, as aging is often associated with decreased physical activity and reduced medication adherence. The solution proposed by this community service team (PKM) involves delivering structured health education and counseling sessions on hypertension. This initiative takes the form of health education provided by a team of nursing lecturers, targeting 34 elderly participants, most of whom are living with hypertension. The method employed in this PKM program includes educational sessions conducted by the implementing team, accompanied by local healthcare workers and involving elderly health cadres from the Purbayan village area.